Sosialisasi Program Bantuan Hukum Gratis Bagi Keluarga: Implementasi dan Tantangan di Pengadilan Agama Kabupaten Bogor - Faris Maulana Akbar; Abdurrahman Hakim; Muhammad Thoriq (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to explore the implementation and challenges of the Free Legal Aid Program for Families in Need within Religious Courts. The research employs a qualitative method using a case study approach, where data is collected through in-depth interviews with judges, lawyers, and recipients of legal aid. The academic debate in this article includes an analysis of the program's effectiveness in meeting the legal needs of the community, as well as the challenges faced, such as a lack of resources and public understanding of their legal rights. The findings indicate that while the program holds significant potential for assisting families in need, various obstacles exist, including social stigma, insufficient program outreach, and administrative challenges that affect the accessibility and quality of legal services. These findings aim to provide insights for future program improvements.